Engineering hollow electrodes for hybrid solar cells for efficient light harvesting and carrier collection. Issue 44 (28th October 2016) - Yin, Peng-Fei; Wang, Jing-Jing; Zhou, Yu-Zhu; Mao, Jing; Qin, Wen-Jing; Qiao, Shi-Zhang; Ling, Tao; Du, Xi-Wen
Abstract : Hybrid-structured solar cells with superior light absorption, charge separation and hole transportation exhibit enhanced photovoltaic performance. Abstract : The organic–inorganic hybrid solar cell (HSC) is regarded as a promising candidate for third-generation solar cells. Currently, their performance hovers at a low level due to the contradiction between the exciton diffusion and light absorption of the organic layer. In the present work, we provide an efficient solution by designing a hollow electrode for the HSC, which contains CdS nanoflake arrays (NFAs) coated with a thin organic active layer and a roof-like metallic electrode. The hollow electrode facilitates light absorption, charge separation, and hole transportation simultaneously, and as a result, the novel HSC outperforms traditional solid and core–shell HSCs. Our work demonstrates that the reasonable design of the electrode structure is of great importance for improving the power conversion efficiency of HSCs.